Sāk vitt ok vītt of verǫld hverja - Koutsomichalis, Marinos (My University, 2026)
'Sāk vitt ok vītt of verǫld hverja' multimedia project performed live at Nordic Music Days 2019, Bodø, NO. https://issuu.com/froe_design/docs/nmd-2019-programbok-endelig